Advanced Hydroinformatic Techniques for the Simulation and Analysis of Water Supply and Distribution Systems - Silvia Meniconi (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The overall objective of this Special Issue is to improve knowledge on developing and using advanced simulation tools in water supply and distribution systems. The final aim is to propose a suitable framework supporting insightful hydraulic mechanisms to help the decision-making processes of water utility managers and practitioners. Contributions to this Special Issue, exploring new research avenues on urban hydraulics and hydroinformatics, will be of great value for both Academia and those water utility stakeholders. On top of this, important social benefits are expected from a number of research objectives that ultimately aim to guarantee a regular supply of clean water at the pressure and quality required at the network consumption points. These objectives include a wide spectrum of subjects, such as demand monitoring and forecasting; network sectorisation; innovative tools for water resources management; leakage detection; system maintenance; transient control; and consumer satisfaction assessment, among others.